(untitled) (The Pakistan Development Review, 1976)
The interest of the policy-maker in social sectors is of a recent origin. All aggregative production functions in the past indicated the existence of a residual factor which was generally imputed to qualitative and quantitative advances in education and training. Other social factors like health were not given the attention they deserved. It took a long time before the economic significance of education could fee reflected in policy-making. Still worse is the case of health sector, the study of which has not been seriously done by economic theorists.